Species Diversity And Distribution Of Planktonic Copepods In The Straits Of Malacca - Ismail, Johan (2001)
Planktonic copepods were collected from 18 stations during JICA/MASDEC Malacca Straits Scientific Expedition, in November 1998 (Northeast monsoon) and April 1999 (Presouthwest monsoon). A total of 88 species of copepods, comprised 4 orders, 17 families and 24 genera were recorded in the Straits o f Malacca. Amongst them eleven species were new records to Malaysian waters. They were Eucalanus subtenuis, Delius nudus, Scolecithricella minor, Clausocalanus farrani, Euchaeta wolfendeni, Centropages sp., Pseudocalanus sp., Lucicutia flavicornis, Candacia tuberculata, Corycaeus longisytis, and Copilia lata. The abundance of the copepod fauna was higher during the presouthwest monsoon (35,429 ind/m3) as compared to the northeast monsoon (20,023 ind/m3). In both monsoon periods, the abundance of